2010
DOI: 10.2215/cjn.08821209
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab as Maintenance Therapy for Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis

Abstract: Results: Disease activity, as measured by a modified Birmingham Vasculitis Activity Score, decreased from a median of 1 at baseline to 0 at 12 (P < 0.001) and 24 months (P ‫؍‬ 0.02). Three patients experienced nonorgan-threatening flares during 708 patient-months of follow-up. Each flare occurred after at least 20 months of follow-up. The percentage of patients on cytotoxic immunosuppression decreased from 87% at baseline to 41% at 12 months (P < 0.001) and 30% at 24 months (P ‫؍‬ 0.002). The percentage of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 32 publications
6
90
1
2
Order By: Relevance
“…Table 1 illustrates the study population, which was comprised of 172 patients who underwent rituximab-induced continuous B cell depletion for maintenance of remission. We did not assign specific diagnoses of GPA or MPA given uncertainties involved in categorizing subsets of ANCA vasculitides (12). Furthermore, it is now becoming clear that ANCA autoantigen specificity may reflect phenotype more accurately than GPA or MPA (16).…”
Section: Statistical Analysesmentioning
confidence: 93%
See 2 more Smart Citations
“…Table 1 illustrates the study population, which was comprised of 172 patients who underwent rituximab-induced continuous B cell depletion for maintenance of remission. We did not assign specific diagnoses of GPA or MPA given uncertainties involved in categorizing subsets of ANCA vasculitides (12). Furthermore, it is now becoming clear that ANCA autoantigen specificity may reflect phenotype more accurately than GPA or MPA (16).…”
Section: Statistical Analysesmentioning
confidence: 93%
“…We included 172 consecutive patients treated between April of 2006 and March of 2013 at the Vasculitis and Glomerulonephritis Clinic in the Nephrology Division at the Massachusetts General Hospital. Patients were considered to have ANCA vasculitis if they had a positive test for PR3-or MPO-ANCA, which was detected by ELISA in the Massachusetts General Hospital ANCA Clinical Laboratory (12), together with a history of clinical and laboratory features consistent with granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), or related variant forms of vasculitis (13). New patients and patients with disease relapse (Birmingham Vasculitis Activity Score [BVAS]-Wegener's Granulomatosis [WG]$3) were included in this retrospective analysis when they were transitioned to continuous maintenance rituximab after undergoing induction therapy and entering full remission (defined as BVAS-WG=0 while on prednisone,10 mg/d).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent case reports suggested that late-onset neutropenia also occurs in rheumatoid arthritis (RA) and pemphigus vulgaris patients treated with rituximab (2,3). In addition, 2 groups observed late-onset neutropenia in a survey of rituximab therapy in patients with antineutrophil cytoplasmic antibodyassociated vasculitis (4,5), emphasizing that late-onset neutropenia is not unique to rituximab-treated patients with hematologic disorders. However, there is currently no published information on how often and why lateonset neutropenia occurs in patients with rheumatic diseases.…”
mentioning
confidence: 99%
“…These autoantibodies participate in the pathogenesis of the disease 2 and are a B lymphocyte target of therapy using rituximab. [3][4][5][6][7][8] In fact, the disorder is now termed ANCA-associated or ANCA vasculitis.…”
mentioning
confidence: 99%